Mobile Internet Adoption in West Africa - Rodriguez-Castelan, Carlos (The World Bank, 2021)
Mobile broadband internet is the main technology through which individuals access the internet in developing countries. Understanding the barriers to broadband adoption is thus a priority in designing policies aiming to expand access and close the digital divide across socioeconomic groups and territories. This paper exploits data from harmonized household expenditure surveys in seven countries in West Africa in 2018/19-a subregion with one of the lowest levels of mobile internet penetration in the world-to identify the main factors that limit mobile broadband internet adoption. Results show that low levels of household consumption and prices of services are two key constraints. One standard deviation increase in household expenditure, about USD 65 per capita per month, is associated with a 6.5 percentage point rise in the probability of adoption, while one standard deviation drop in the price of mobile internet services, about USD 3.60, increases the probability of adoption by 2.4 percentage points. Other determinants include demographic characteristics (sex, age, language, urban location), socioeconomic features (educational attainment, sector of employment), and other factors linked to policy (access to electricity, ownership of assets, alternative means of internet access). Results are robust to specifications focusing only in areas with mobile internet coverage (3G)